MySoundtrack: a tool for personalized and adaptive music listening while playing games - Bezerra, Daniel Filgueira; Calegario, Filipe; Cabral, Giordano; Ramalho, Geber (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2021: Anais Estendidos do XX Simpósio Brasileiro de Jogos e Entretenimento DigitalDO - 10.5753/sbgames_estendido.2021.19663, 2021)
Adaptive soundtrack design for video games is an ever-evolving field of study: games that modify its music depending on what is happening around and with the player. Meanwhile, independent game developers struggle with composition of soundtracks, and adaptive soundtrack tools are not accessible to them, mostly because of their complexity. This forces most of them to collage soundtracks with permissive licenses they find online. Besides, there is a growing habit of players to mute the game's original soundtrack to listen to their own songs. This paper introduces MySoundtrack, an asset for Unity that allows the player to keep playing while listening to Spotify songs, chosen according both to the player musical preferences and to the intended emotions on each moment in the game. We review existing approaches on adaptive soundtracks, explain how MySoundtrack's prototype works and its design choices, and discuss future plans for the tool. Validation so far indicates interest and curiosity by game developers and players, indicating the relevance of the proposed plug-in.